Physical inactivity and its associated factors among pre-retirement government healthcare workers in Kuala Lumpur, Malaysia - Dapari, Rahmat; Abdul Wahab, Mohamad Rabani; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (BioMed Central, 2024)
Introduction: The rising worldwide concern of Non-Communicable Diseases (NCD) is alarming as it is associated with 80% of annual global mortality. NCD threat is rising due to, among others, the increasing ageing population, thus putting the efforts to promote health ageing at the forefront of many countries’ health agenda. Physical activity has been recognised as one of the significant factors in the pursuit of healthy ageing. Nevertheless, approximately one third of individuals in Malaysia are physically inactive. The aim of this study is to determine the prevalence of physical inactivity and its associated factors among pre-retirement government healthcare workers. Methods: This cross-sectional study was conducted from May to June 2023 among pre-retirement government healthcare workers in Kuala Lumpur, Malaysia. The sample size required was 233 and proportionate random sampling was used to recruit potential respondents who answered self-administered online questionnaires. Global Physical Activity Questionnaire (GPAQ) was used to measure the level of physical activity and data analysis was performed using SPSS version 29. Results: A total of 214 complete responses were received from the 233 questionnaires distributed, giving a response rate of 91.8%. The prevalence of physical inactivity among pre-retirement healthcare workers was 39.7% as compare only 29.9% in general population. Significant predictors for physical inactivity included higher education levels (SPM, STPM, or certificate holders) (AOR = 13.4, 95% CI: 2.47–72.65), non-Malay ethinicity (AOR = 4.7, 95% CI: 1.23–18.38), personal barriers (AOR = 1.6, 95% CI:1.35–1.79), social barriers (AOR = 1.21, 95% CI: 1.06–1.39), and physical environment barriers (AOR = 1.468, 95% CI: 1.221–1.765). Conclusion: This study shows a worrying prevalence of physical inactivity among pre-retirement healthcare workers that is even higher than the general population in Malaysia. The findings highlight the importance of focusing the preventive strategies among non-Malay workers and those with lower education levels. It is also vital to address all the physical, social, and environmental barriers towards physical inactivity. By prioritising these factors, employers and stakeholders will be able to establish better workplace health promotion and address the issue of physical inactivity more efficiently.